DO IN UTERO SHOCKS HAVE ADVERSE EFFECTS ON CHILD HEALTH OUTCOMES AND CAN WELFARE SCHEMES AMELIORATE SUCH EFFECTS? EVIDENCE FROM ANDHRA PRADESH, INDIA. Issue 6 (27th November 2017) - Ahmed, Salma; Ray, Ranjan
Summary: This study aimed to assess whether shocks experienced by children in the mother's womb can have an adverse effect on their future health, and whether these effects can be ameliorated by government welfare schemes. Data were taken from three phases of the Young Lives Survey carried out in the Indian state of Andhra Pradesh in 2002, 2007 and 2009–2010. Different types of in utero shock were distinguished from the data. Using ordinary least squares (OLS) estimation, it was observed that multiple in utero shocks reduced children's weight-for-age and height-for-age z -scores by 0.07–0.08 and 0.08–0.15 units respectively. The roles of two Indian government welfare schemes – the Midday Meal Scheme (MDMS) and the National Rural Employment Guarantee Scheme (NREGS) – in mitigating the adverse effects of in utero shocks were examined. While the effect of the MDMS was statistically insignificant, that of the NREGS was significant. Although not designed to protect child health, the NREGS has been playing a more effective role than the MDMS in acting as a buffer against the damaging effects of in utero shocks on child health. The study points to the need for greater co-ordination between the two welfare schemes.